EXPERIMENTAL PHARMACOLOGY OF BHARANGI [CLERODENDRUMSERRATUM(LINN.) MOON]- A REVIEW UPDATE - Choudhari Deepali D.; Y. R. Kulkarni (International Journal of Applied Ayurved Research, 2019)
Research in the field of medicinal plants can be broadly classified as Literature research, Fundamental research, Experimental research and Clinical research. Enrichment of Dravyaguna (materiamedica) depends to a great extent on all the above types of researches.Bharangi[Clerodendrumserratum(Linn.) Moon] a medicinal plant mentioned in Ayurveda classics has proven to possess multiple pharmacological activities. Ethno-pharmacological significance of Bharangi is due to its anti-inflammatory, anti-allergic, anti-asthmatic, anti-histaminic, antimicrobial, anticancer, antioxidant, anti-diabetic, anti-tussive, spermicidal and CNS depressant activity. Bharangi root, stem, stem-bark and leaves have been used traditionally for various ailments. Clerodendrumserratum(Linn.) Moon has been studied for different pharmacological activities, using different parts ( root ,stem, leaf) and using various animal models. Clerodendrumserratum(Linn.) Moonwith immense pharmacological activities has been reviewed with an aim to provide a reference source to plan further research strategy on the plant for the unexplored Pharmacological uses of Clerodendrumserratum(Linn.) Moon.The present review encompasses the recent pre-clinical studies ofBharangi[Clerodendrumserratum(Linn.) Moon] carried out in the field of Experimental Pharmacology and its further scope in clinical research.